Factors Affecting the Business Efficiency of Enterprises Under the Vietnam General Department of Defence Industry (International Journal of Scientific Research and Management (IJSRM), 2024)
Enterprises under the General Department of Defense Industry (GDDI) play an important role in the defense industry of Vietnam, yet so far their business operations has had low efficiency. Therefore, it is necessary to clarify the factors affecting the business efficiency of GDDI enterprises, thereby having timely solutions for the new political and economic situation of the country. Previous studies have only focused on individual GDDI enterprises of different scale and resources and haven’t been able to come up with a systemic solution. This article fills the gaps of previous studies by identifying factors affecting the business efficiency of GDDI enterprises between 2016 and 2021. By using quantitative research and linear regression model, the author identified factors affecting the business efficiency of GDDI enterprises and gave recommendations of financial solutions to improve business efficiency for these enterprises.